A Twice Electrochemical-Etching Method to Fabricate Superhydrophobic-Superhydrophilic Patterns for Biomimetic Fog Harvest - Xiaolong Yang (Nature Portfolio, 2017)
Abstract Superhydrophobic-superhydrophilic patterned surfaces have attracted more and more attention due to their great potential applications in the fog harvest process. In this work, we developed a simple and universal electrochemical-etching method to fabricate the superhydrophobic-superhydrophilic patterned surface on metal superhydrophobic substrates. The anti-electrochemical corrosion property of superhydrophobic substrates and the dependence of electrochemical etching potential on the wettability of the fabricated dimples were investigated on Al samples. Results showed that high etching potential was beneficial for efficiently producing a uniform superhydrophilic dimple. Fabrication of long-term superhydrophilic dimples on the Al superhydrophobic substrate was achieved by combining the masked electrochemical etching and boiling-water immersion methods. A long-term wedge-shaped superhydrophilic dimple array was fabricated on a superhydrophobic surface. The fog harvest test showed that the surface with a wedge-shaped pattern array had high water collection efficiency. Condensing water on the pattern was easy to converge and depart due to the internal Laplace pressure gradient of the liquid and the contact angle hysteresis contrast on the surface. The Furmidge equation was applied to explain the droplet departing mechanism and to control the departing volume. The fabrication technique and research of the fog harvest process may guide the design of new water collection devices.